Low serum tryptophan predicts higher mortality in cardiovascular disease - Murr, Christian; Grammer, Tanja B.; Kleber, Marcus E.; März, Winfried (European journal of clinical investigation, 2015)
Background The essential amino acid tryptophan is required for protein synthesis and formation of the neurotransmitter serotonin and may exert immunoregulatory functions. An accelerated tryptophan breakdown rate is associated with inflammation and immune activation. Materials and methods Serum concentrations of free tryptophan, neopterin and high-sensitivity C-reactive protein (hsCRP) were measured in 1196 patients with coronary artery disease (CAD) derived from the LUdwigshafen RIsk and Cardiovascular Health (LURIC) study. Results Tryptophan concentrations did not differ between patients with (mean ± SD: 40·1 ± 9·8 μM) or without (42·3 ± 23·9 μM; not significant, Welch's test) angiographic CAD, but patients with CAD had higher neopterin (9·1 ± 8·2 nM) and hsCRP (9·3 ± 18·5 mg/L) concentrations compared to patients without (neopterin: 7·6 ± 4·7 nM, hsCRP: 5·8 ± 7·6 mg/L; both P < 0·0001). There existed an inverse correlation between serum tryptophan and neopterin (Spearman's rank correlation: rs = -0·273) and hsCRP (rs = -0·163; both P < 0·0001) concentrations. Median observation time was 10·5 years, and 385 patients had died, including 244 patients due to cardiovascular and 132 due to noncardiovascular causes. After adjustments for cardiovascular risk factors and other possible confounders, the hazard ratio (with 95% CI) in the first tryptophan quartile of the study population was 1·51 (1·19-1·90; P = 0·0006) for total mortality, 1·41 (1·05-1·89; P = 0·0224) for cardiovascular and 1·79 (1·20-2·67; P = 0·0042) for noncardiovascular mortalities, respectively, thus indicating a significantly higher risk of death in patients with tryptophan concentrations < 34 μM. Conclusions Low serum tryptophan in patients with CAD is associated with immune activation and indicates reduced life expectancy.
Gesehen am 03.12.2018